Sterilization of liquid foods by pulsed electric fields–an innovative ultra-high temperature process - Reineke, Kai; Schottroff, Felix; Meneses, Nicolas; Knorr, Dietrich (Frontiers in Microbiology, 2015)
The intention of this study was to investigate the inactivation of endospores by a combined thermal and pulsed electric field (PEF) treatment. Therefore, self-cultivated spores of Bacillus subtilis and commercial Geobacillus stearothermophilus spores with certified heat resistance were utilized. Spores of both strains were suspended in saline water (5.3 mS cm−1), skim milk (0.3% fat; 5.3 mS cm−1) and fresh prepared carrot juice (7.73 mS cm−1). The combination of moderate preheating (70–90°C) and an insulated PEF-chamber, combined with a holding tube (65 cm) and a heat exchanger for cooling, enabled a rapid heat up to 105–140°C (measured above the PEF chamber) within 92.2–368.9 μs. To compare the PEF process with a pure thermal inactivation, each spore suspension was heat treated in thin glass capillaries and D-values from 90 to 130°C and its corresponding z-values were calculated. For a comparison of the inactivation data, F-values for the temperature fields of both processes were calculated by using computational fluid dynamics (CFD). A preheating of saline water to 70°C with a flow rate of 5 l h−1, a frequency of 150 Hz and an energy input of 226.5 kJ kg−1, resulted in a measured outlet temperature of 117°C and a 4.67 log10 inactivation of B. subtilis. The thermal process with identical F-value caused only a 3.71 log10 inactivation. This synergism of moderate preheating and PEF was even more pronounced for G. stearothermophilus spores in saline water. A preheating to 95°C and an energy input of 144 kJ kg−1 resulted in an outlet temperature of 126°C and a 3.28 log10 inactivation, whereas nearly no inactivation (0.2 log10) was achieved during the thermal treatment. Hence, the PEF technology was evaluated as an alternative ultra-high temperature process. However, for an industrial scale application of this process for sterilization, optimization of the treatment chamber design is needed to reduce the occurring inhomogeneous temperature fields.